Modulation of AR-FGF-2-TGF beta Axis by Cosmos caudatus Suppresses Prostatic Epithelial Proliferation in a BPH Rat Model: A Comparative Study with Finasteride - Sahara, Nita; Mudigdo, Ambar; Wasita, Brian; Pamungkasari, Eti Poncorini; Dirgahayu, Paramasari; Cilmiaty, Risya (Journal of Multidisciplinary Applied Natural Science, 2026)
Benign prostatic hyperplasia (BPH) progression is critically influenced by the androgen receptor (AR), Fibroblast growth factor-2 (FGF-2), and transforming growth factor-β (TGF-β) signaling axis. Although finasteride (FIN) is the standard therapeutic agent, its use is limited by adverse effects. This study evaluated the efficacy of Cosmos caudatus (CC) extract, administered alone or in combination with FIN, in modulating the AR–FGF-2–TGF-β axis in a testosterone-induced BPH rat model. Rats were divided into five groups (n = 6): Normal (N), BPH control (KN), FIN (KP; 0.44 mg/kg), CC extract (P1; 250 mg/kg), and combination (P2; CC 250 mg/kg + FIN 0.44 mg/kg). Prostatic AR, FGF-2, and TGF-β expression was analyzed using immunohistochemistry (IHC) with H-score quantification. Both KP and P1 significantly reduced AR (KP: 112 ± 15; P1: 105 ± 12 vs KN: 195 ± 18, p < 0.05) and FGF-2 (KP: 98 ± 14; P1: 92 ± 11 vs KN: 180 ± 20, p < 0.05), approaching normal values (AR N: 90 ± 10; FGF-2 N: 85 ± 9). In contrast, combination therapy (P2) failed to suppress AR (188 ± 17, p = 0.936) and FGF-2 (175 ± 19, p = 0.870) and induced a significant increase in TGF-β (P2: 145 ± 16 vs KN: 110 ± 12, p < 0.05). All treatment groups showed reduced epithelial thickness and prostate index (p < 0.05). These findings indicate that CC extract alone exerts therapeutic effects comparable to FIN by modulating the AR–FGF-2 axis, whereas combining it with FIN disrupts pathway regulation and promotes a pro-fibrotic response. The study supports the potential of CC extract as an effective alternative for BPH management without pharmacologic complications.